Efficacy of chloramine-T as a treatment for amoebic gill disease (AGD) in marine Atlantic salmon (Salmo salar L. ) - Harris, J; Powell, MD; Attard, M; Green, TJ (Aquaculture Research, 2004)
Atlantic salmon with amoebic gill disease (AGD) were treated with chloramine-T to compare its effectiveness with that of freshwater bathing. In 250-L tank trials, treatment of seawater with chloramine-T reduced amoeba density on the gills to levels significantly lower than when treated with seawater alone. There was no further change in amoeba levels in fish bathed for 3 or 6 h compared with 1 h of treatment. Plasma lactate levels in fish bathed in chloramine-T for 6 h showed no differences across treatments. In 1000-L tank trials using freshwater alone or seawater with chloramine-T, significant reductions in amoeba density occurred compared with pre-bath levels. Histological analysis of gill tissue revealed AGD lesion levels to increase, then to return to pre-bath levels within 1 week for freshwater-treated fish, while chloramine-T- and seawater-treated fish had higher levels of AGD lesions from 2 weeks post bathing. Immunodot-blot data indicated an initial significant increase in prevalence of lesions in seawater and chloramine-T-treated fish, which declined to levels significantly lower than pre-bath levels by 3 weeks post bathing, compared with the freshwater-treated fish, which had significantly lower levels than controls by 2 weeks post bathing. At reducing amoeba density, it is apparent that bathing AGD-affected Atlantic salmon in seawater with chloramine-T proved at least as effective as freshwater.